(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The ideas, rules, and laws of human education were initially based on stories, pandnoms, written monuments, andfolklore, and later on, they strengthen their position as an independent science.Indeed, our ancestors paid special attention to child education from time immemorial. Imam al-Bukhari, -Isa at-Termizny, Berunny,Az-Zamakhshari, Navoi, Babur, Ogahi, great scientists, writers, virtuous people like Abdurauf Fitrat, Abdulhamid Cholpon, wrotemany works on education. "The City of Virtuous People" by Faro Bey, who is considered the founder of Eastern pedagogy, "QutadguBilig" by Yusuf Khos Hajib, "Mahbub ul-Qulub" by Alisher Navoi, "Nightmare" by Kaikovus, and "Futuvvatnamai Sultani" by VaizKoshfi are proof of this. It is known from history that Eastern pedagogy once flourished. When the German scientist Herler said, "TheEast is the teacher of Europe", he probably meant this period of development.